Ethical fashion brands : promotion approach or a real value - Guedes, Maria da Graça (2011)
Ethical fashion appears as a conscious consumption movement in the 90’s. It covers product offers and styles increasingly diverse. This movement has become a sustainable brand strategy, and so the number of ethical brands grew significantly in recent years, as well as their turnover. Consumers find in ethical brands a set of values that fulfill not only their need for style but also give the opportunity, through consumption, to contribute to environmental preservation, to the improvement of working conditions and better of quality of life in their countries and in less developed countries. Alternative marketing plays a key role in creating the market image of ethical fashion brands, by assuring transparency and clarity of messages, credibility and continuity, so that their differentiation factors can be step by step assimilated and understood by consumers. The study of a set of ethical fashion brands allowed to observe that these usually at the stage of market entry tend towards opting to offer a specific value, communicated clearly. Progressively, the elements of brand differentiation evolve into integrated value systems, which involve the development of complex organizational models. The market growing demand for ethical fashion brands and products suggests that ethics in fashion have a tendency to be a requirement in a near future for most brands. We argue that the market trends within a relatively short time point towards the adoption of ethical principles by the fashion brands and towards the adoption of social responsibility by companies that manage these brands. These two aspects will be an essential condition for competitiveness in order to survive in the global market. This trend could be considered similar to those that have determined the emergency requirement of other competitive factors such as quality. While the competitive material or technological may be spread at a relatively rapid rate and with similar characteristics across the value chain; the strategies focused on values such as ethics and Corporate Social Responsibility, however, are substantially more complex and can vary according to nature and depth. Thus, it may be considered that instead of tackling the fashion brands in terms of their competitiveness restrictions, these values appear as an extension of their normal elements of differentiation as style and fashion image.